Profil pressionnel de l’adolescent en milieu scolaire à Lubumbashi, République Démocratique du Congo - Kakoma, Placide Kambola (Pan Afr Med J, 2018)
INTRODUCTION: This study aimed to highlight blood pressure (BP) profile in adolescents aged 15-19 years at school in Lubumbashi, Democratic Republic of the Congo. METHODS: We conducted a cross-sectional study of adolescents aged 15-19 years through random sampling of the secondary schools in Lubumbashi during the school years 2013-14, 2014-15 and 2015-16. Blood pressure was measured three times in the same day. RESULTS: Our study included 1766 adolescents aged 15-19 years, of whom 995 were females and 771 boys. Boys’ systolic blood pressure was significantly higher than that of girls aged 17, 18 and 19 years. Diastolic blood pressure was not statistically different in all different age groups in both sexes. On the other hand, in both sexes, systolic blood pressure was significantly correlated with body weight, size, body mass index, waist size and heart rate. With regard to diastolic blood pressure, significant correlations were found with body weight and body mass index in girls while heart rate was significantly correlated in both sexes. CONCLUSION: Despite the potential weaknesses of the present study with special regard to its cross-sectional design and to BP measures in the same day, collected data could help health authorities to adopt a national hypertension prevention strategy.